2007
DOI: 10.4028/0-87849-428-6.1028
|View full text |Cite
|
Sign up to set email alerts
|

Novel Separation Technique of Particle Reinforced Metal Matrix Composites by Fused Deposition Method

Abstract: Abstract. To develop a novel separation technique of matrix alloys from metal matrix composite, separation experiments for various kinds of particle reinforced metal matrix composites (PRMMCs) were carried out. The Al-4mass%Cu alloy, Al-7mass%Si alloy and cast iron were used as matrix. The SiC particles (particle size: 75µm) and Al 2 O 3 particles (particle size: 120µm) were used as reinforcement. The PRMMC specimen was placed in a silica tube container with a small nozzle (nozzle size: 0.75mm) at the bottom a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The separation experiments using the container with various nozzle shapes 6 were carried out. The effect of applied pressure on nozzle filtering method has been reported by Mizumoto et al (2007) and the applied pressure in this work was 0.25 MPa.…”
Section: Effect Of Nozzle Shape On the Separation Processmentioning
confidence: 79%
See 2 more Smart Citations
“…The separation experiments using the container with various nozzle shapes 6 were carried out. The effect of applied pressure on nozzle filtering method has been reported by Mizumoto et al (2007) and the applied pressure in this work was 0.25 MPa.…”
Section: Effect Of Nozzle Shape On the Separation Processmentioning
confidence: 79%
“…In order 4 to investigate the effect of reactivity of the container material with the molten matrix alloy on the separation process, the containers were made of silica which was reactive to the molten aluminum alloy, or KC carbon ceramic which was unreactive. Mizumoto et al (2007) have reported an optimum nozzle size for nozzle filtering method and the nozzle size was 0.75mm in diameter. The PRMMC specimen was remelted at 1273K by H.F induction heating when silica tube was used as the container material.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation